Comparison of the Effectiveness of Traditional Teaching and Case-Based Teaching in the Enhancement of Academic Motivation and Learning in Nursing Student’s Physiology Course - A Experimental Study - Khadijeh Moradbeygi; Fatemeh Khodadadi; Jomehzadeh; Maryam Jafar Sameri; Seyyed Mohammad Ali Malaeke (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī, 2025)
Introduction: Medical education today is associated with numerous complexities in both theoretical and clinical learning environments. Consequently, educational planners and practitioners face with limitations in empowering students to enter the healthcare system. The present study aimed to compare the impact of teaching physiology through traditional methods versus case-based teaching on academic motivation of nursing students at Abadan University of Medical Sciences to address potential educational needs and enhance the quality of medical education. Methods: The present study is an experimental intervention research conducted during the second semester of the 2022-2023 academic year on freshmen undergraduate nursing students at Abadan University of Medical Sciences, Iran. In the present study, all students who selected the physiology course participated and were randomly divided into two groups—traditional teaching and case-based teaching—with gender matching considered. At the beginning of the teaching period, a pre-test was administered to all students, and they were given class assignments throughout the academic semester. At the end of the semester, following the final exam, academic motivation questionnaire was completed by students. Data were collected using Harter's standard academic motivation questionnaire and final exam scores and were analyzed using independent t-tests and the Mann-Whitney U test through SPSS (Version 16) software. Results: A total of 26 nursing students participated in the study, of whom 53.8% (14 individuals) were female and 46.2% (12 individuals) were male, all participants were single. The findings indicated a moderate level of academic motivation, with mean scores of 87.53 for the case-based teaching group and 68.84 for the traditional teaching group. The results demonstrated that the average academic motivation score was significantly higher in the case-based teaching group compared to the traditional teaching group (P=0.023). Moreover, the grades of class assignments and end-of-semester scores in the case-based group were significantly higher than in the traditional approach group (P=0.006). Conclusion: Data analysis revealed that academic motivation score of students in cased-based teaching were significantly higher than that traditional teaching. These findings suggest that employing active and interactive teaching methods, such as case-based learning, can be an effective strategy for enhancing nursing students' academic motivation. It is recommended that modern teaching approaches be incorporated into the curriculum planning of basic medical science courses.